Phytoseiid mites (Acari: Phytoseiidae) from vineyards in Rio Grande do Sul State, Brazil - Ferla, Noeli Juarez; Johann, Liana; Klock, Crisna; Majolo, Fernanda; Botton, Marcos (Zootaxa, 2011)
In this paper we report on the phytoseiid mites associated with grapevine in the state of Rio Grande do Sul, Brazil, which may be natural enemies of the pest mites Calepitrimerus vitis, Colomerus vitis (Eriophyidae), Panonychus ulmi (Tetranychidae) and Polyphagotarsonemus latus (Tarsonemidae). A total of 1,538 phytoseiid mites belonging to 30 species was found. Neoseiulus californicus showed the highest abundance with 844 specimens, followed by Euseius inouei, with 274 specimens. The majority of mites (83%) were observed on vine plants and 17% on the uncultivated plants. Of the 30 species found, 22 were observed on vine plants, 15 on the uncultivated plants and 10 species on both types of plants. When the phytoseiid species were collected in both places, on vine and on the associated plants, greater populations were found on vine plants.